Wheat grains damaged by Fusarium graminearum: alterations in yield, toxicity and protein composition - Ortega, Leonel Maximilano (2019)
The aim of this study was to investigate alterations on wheat grains, in relation to yield and quality parameters, such as infection degree, protein composition and toxicity caused by isolates of Fusarium graminearum with different aggressiveness. The disease degree on wheat samples was evaluated by the parameters like incidence, severity, damaged kernels percentage, yield, deoxynivalenol content and protein constitution, which were analyzed employing accurate quantitative statistics. High and positive correlations among the disease degree parameters were found, as well as negative correlations between them and yield, meanwhile, the total protein content was correlated with yield but was not correlated with the disease degree. The data analysis showed that the effect of the isolate was more significant than the cultivar in the disease degree for almost all the studied variables. The variability in the content of the deoxynivalenol mycotoxin showed a positive tendency in relation to the infection degree. As a novel approach, the aggressiveness of the different isolates ranged from high to low allowing us to evaluate a wide range of the aftereffects of the disease.